Communication Development in Children with Intellectual Disabilities: Implications for Education and Psychology - Akmaral, Akzholova; Kyalbek, Akmatov; Guldina, Kamalova; Abdikerim, Muratov; Khalima, Kidirbayeva; Yerzhan, Yergeshov (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
This article discusses communication disorders in children and adolescents with mild intellectual disability and the relationship between communication, social interaction, and development. A theoretical and methodological framework is developed, including a structural-functional communication model, and the psychological models associated with communication disorders are presented. This study demonstrates that communication disorders are influenced by three main factors: emotional needs, regulative, and cognitive, which are suggested to reflect predominant communication styles. Data were collected using clinical observations, standardized diagnostic tools, and formal psychological measures. For example, standardized tests included the Peabody Picture Vocabulary Test, CELF, Wechsler Intelligence Scale for Children, and Vineland Adaptive Behavior Scales, aiming better to understand the child's communication and adaptive behavior. The findings suggest that it is important to consider family dynamics and composition when looking at the development of communication disorders. In addition, age-related differences and dominant communication styles were presented in what educating children/adolescents with disabilities looks like in inclusive education. Some practical interventions discussed included differentiated instructional approaches, speech and language therapy, peer-mediated interventions, and evidence-based social skills intervention programs. The goal of the intervention is to improve speech and language skills, improve the child's social interaction, and improve children's academic performance in school settings where they support the need for inclusion while meeting the needs of the child. In conclusion, the study validates the hypothesis regarding the significant role of social emotions in preschool children's communication process. The methodology developed for developing social emotions in preschool children effectively enhances emotional spheres and normalizes peer relationships. The article underscores the need for understanding the psychodynamic and poly-structural continuum of communication disorders, providing a theoretical basis for optimal conditions in the socialization of children with mild intellectual disability.